Kajian Keislamanan dan Kajian Ilmu Sosial Pendekatan dan Implikasi - Siti Bariyati; Herliyana Herliyana; Karsani Karsani; Agus Rifki Ridwan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This journal discusses the importance of integrating islamic values within then study of social sciences Through an interdisciplinary approach, this research aims to explore how islamic principles can enrich then understanding of social, cultural, and economic aspects in the context of modern society.